Hepatitis b virus-related hepatocellular carcinoma in south africa: investigations into the risk profile of a previously unscreened population from the Western Cape - Chotun, Bibi Nafiisah (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.